(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This article covers essential aspects of caring for a newborn in their first year, including nutrition, sleep, developmental milestones, emotional wellbeing, and practical daily care. It emphasizes the importance of breastfeeding, establishing healthy sleep patterns, monitoring developmental milestones, fostering emotional bonds, and maintaining proper hygiene.